Why is my phlegm green? A rare case of bronchobiliary fistula - Deepak Sasikumar; Vikramaditya Rawat; Meghraj Ingle; Shamsher Singh Chauhan; Chintan Tailor; Saiprasad Lad; Yatin Lunagariya; Shivani Chopra; Vinay Borkar; Mit Shah; Motij Kumar Dalai (Society of Gastrointestinal Intervention, 2024)
Bronchobiliary fistula is a very rare entity that presents with bilioptysis. We present a noteworthy case involving a patient with portal cavernoma cholangiopathy complicated by cholangitis and bronchobiliary fistula. The diagnosis was established through high-resolution computed tomography of the thorax and bronchoscopic evaluation. Subsequently, the patient underwent endoscopic retrograde cholangiopancreatography with stenting of the common bile duct. Remarkably, the bronchobiliary fistula resolved 1 month after the procedure.